Association of nutritional status and laboratory parameters with heart failure among children with congenital heart disease - Herlina Dimiati; Zaki Akbar (AcTion: Aceh Nutrition Journal, 2025)
Congenital Heart Disease (CHD) is a structural and functional abnormality of the heart that occurs at birth. If left untreated, CHD can lead to heart failure, respiratory infection, and malnutrition. Data on nutritional status, anemia, leukocyte count, and serum 25-hydroxy vitamin D [25(OH)D] levels in pediatric CHD patients with heart failure remain limited.  This study aimed to analyze the correlation between nutritional status, anemia, leukocyte count, and serum 25-Hydroxy vitamin D levels, and heart failure in children with CHD. A cross-sectional study was conducted at three hospitals in Banda Aceh from August 1, 2022, to July 31, 2023. Pediatric patients with CHD underwent anthropometric, echocardiographic, and laboratory examinations. The exclusion criteria included renal, urinary, endocrine, and hematologic-oncological disorders. Data were analyzed using SPSS version 26.0, and the Mann–Whitney U test was applied for nonparametric variables. Results: Of the 128 patients with CHD (46.1% men), 78.9% had heart failure. Poor nutritional status was found in 49.2% of patients, and anemia in 51.6%, with many showing abnormal leukocyte counts and low serum 25(OH)D levels. Low serum 25(OH)D levels (p=0.010; OR=6.7) and abnormal leukocyte counts (p=0.000; OR=55.6) were significantly associated with heart failure. In conclusion, low serum 25(OH)D levels and abnormal leukocyte counts significantly increase the risk of heart failure in children with CHD.